Deposition and paleo-oceanographic significance of the Late Silurian laminated and bioturbated mudstone in the English Lake District, northwest of England - Salam, Abdus; Kelling, Gilbert (Journal of Himalayan Earth Sciences, 1993)
The Late Silurian (Wenlock) laminated and bioturbated mudstones of the Lake District basin, northwest of England are genetically not different and most likely both resulted from slow and continuous sedimentation but in different bottom water conditions. The deposition of laminated mudstone took place in a density stratified basin. This density stratification produced anoxic bottom water conditions which caused preservation of fine lamination. The bioturbated mudstones display either complete or partial bioturbation, associated with horizontal burrows, indicating slow sedimentation in oxygenated bottom water conditions. The interbedding of bioturbated mudstone with laminated mudstone indicated periodic return of the basin to oxygenated conditions which might have caused by renewed bottom circulations and/or reduction in the supply of organic material.